PENGARUH MEDIA BOLA PUTAR BERGAMBAR TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK PERMATA BUNDA KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Dzikra Wahyuni; Zulkifli N Zulkifli N; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Early childhood education is an effort to stimulate the development of children to be more optimal. One of the aspects of early childhood development that needs attention in TK Permata Bunda is the ability to speak, because based on the results of the survey there is still a child's delay in children's speaking ability and lack of learning media that support to develop children's speaking ability. This study aims to determine the effect of pictorial spinning ball media on the ability to speak children aged 5-6 years in TK Permata Bunda Subdistrict Batang Peranap Regency Indragiri Hulu. The research used experimental method with one group pre-test post-test design. The sample used in this study were 21 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 16. The research hypothesis is that there the effect of the pictorial spinning ball media toward the speaking ability of children aged 5-6 years in tk permata bunda subdistrict batang peranap regency indragiri hulu. Based on data analysis known thitung= 18,362> ttabel = 2.086 with Sig. (2-tailed) = 0,000. Because Sig <0,05 it can be concluded that there are differences in the ability of children to the speaking ability before and after given the pictorial spinning ball media . Based on the data analysis, there is the effect of the pictorial spinning ball media toward the speaking ability of children aged 5-6 years in TK Permata Bunda Subdistrict Batang Peranap Regency Indragiri Hulu which is significant at 43.50%.Keyword: Speaking Ability, Instructional Media